Development of a Problem-Based Learning (PBL) Ethnoscience E-Module on the Biodiversity of Herbal Plants to Enhance Junior High School Students Critical Thinking and Environmental Literacy - Nurmasitoh, Qonita Amalia; Sudarmin, Sudarmin; Ngabekti, Sri; Irsadi, Andin; Sutopo, Agung (Universitas Negeri Semarang, 2025)
This study aims to develop and validate an ethnoscience-based Problem-Based Learning (PBL) e-module on the biodiversity of herbal plants to enhance junior high school students’ critical thinking and environmental literacy. The research used a modified 4D development model (Define, Design, Develop, Disseminate) involving content analysis, expert validation, and practicality testing. The e-module integrates local cultural knowledge with science learning through contextual material and interactive problem-solving activities. Validation was conducted by subject matter and media experts, while practicality was tested by one science teacher and 25 students. Results show the e-module received a content validity score of 90.34% (very valid) and a media validity score of 78.62% (valid). The characteristics assessment by three experts yielded an overall score of 92.69%, categorized as highly suitable for educational use. Practicality scores from teacher and student evaluations were 92.88% and 91.42%, respectively, indicating that the module is easy to use, relevant, and engaging. The findings conclude that the e-module is pedagogically appropriate, practical, and effectively integrates local wisdom into science learning. It supports the development of students’ critical thinking and environmental awareness and can be used as an innovative instructional resource in junior high school science education.